A feasibility study of application of solution prepared by mixing castor oil and turmeric powder to prevent infection with leptospirosis in Ambach village, Surat, Gujarat, India - Kavishvar, Abhay; Verma, Mamtarani (International Journal Of Community Medicine And Public Health, 2017)
Background: Leptospirosis is an acute infection caused by spirochetes belonging to the genus leptospira that can lead to multiple organ involvement and fatal complications. Objectives were to study the acceptance solution prepared by mixing turmeric powder with castor oil, a protective measure against leptospirosis and the feasibility of use of that measure at mass level. Methods:Study was conducted in Ambach village. Group discussion in the meeting at Community Center as well as in the farm when at risk people were actually at work was conducted in the month of June-July 2008. Application of Castor oil and turmeric solution (CT solution) was demonstrated. Solution or a paste prepared by mixing turmeric and castor oil should be applied on the whole surface of both the legs which comes in contact with water in the field. All those who go to field should apply it and provide the feedback in the next group meeting. No statistical tests were applied and results were obtained simply as their feedback. Results: In the form of feedback were from farm workers on inquiring about the trial.1. Families tried it but did not ask for more amount of such solution. 2. It disappeared quickly hence of no use. Conclusions:It can be concluded that farmers, agricultural labourers and other people are not yet prepared to adopt personal protective measures which they feel is not effective, requires daily and regular application and is not affordable. Other known options like early detection and prompt treatment and chemoprophylaxis can be better available as and when sought.